Strength Training Among Male Master Cyclists—Practices, Challenges, and Rationales - Vidar Vikestad; Terje Dalen (Journal of Functional Morphology and Kinesiology)
Background: Cycling performance declines with age due to reduced aerobic capacity, along with reductions in muscle mass and bone density. Strength training can help counter these effects. This study aims to explore the strength training practices, challenges, and decision-making rationale of male master cyclists to optimize performance and health as they age. Methods: A total of 555 male master cyclists aged 35 and above completed an online questionnaire, distributed via social media platforms, that included Likert-type, single- and multiple-selection, and open-ended questions. Participants were then divided into two age groups: 35–49 years (n = 359) and ≥50 years (n = 196). Analyses involved descriptive statistics, Wilcoxon signed-rank tests, Mann–Whitney U-tests, and chi-square tests, with qualitative data analyzed using content analysis. Results: More cyclists engaged in strength training during the off-/pre-season, with a significant reduction in both frequency and the number of cyclists engaging in strength training during the race season. The strength training practice was focused mainly on core and lower body, employing hypertrophy and maximal strength training methods. Key challenges included fatigue induced by strength training and limited time to perform strength training. The main rationale for the strength training revolved around improving cycling performance, reducing injury risk, and the health benefits of strength training. Both age categories, but the older group in particular, reported bone health as a primary rationale for strength training. Conclusions: While strength training offers performance and health benefits, issues of fatigue and time constraints remain substantial, suggesting the need for tailored training programs to improve adherence and effectiveness.